Hnilcze - moja kresowa wieś = Hnilcze - my borderland village - Srokowski, Stanisław (1936- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This is a short monograph of one of the largest villages in the Tarnopol Province. Before World War II, its population amounted to about 3500 residents: Poles, Ukrainians and Jews. This village was called Hnilcze (Pidhaitsi County). The study shortly presents its history, which began in 15th or even 14th century after the birth of Christ. Its turbulent chapters are characteristic for those borderlands.
Keywords: Hnilcze (pow. podhajecki); village; attack; crime; war; night; Poles; Ukrainians; Jews; wieś polska; atak; wojna; Polacy; Ukraińcy; Żydzi